Five porous zinc(ii) coordination polymers functionalized with amide groups: cooperative and size-selective catalysis. Issue 40 (28th October 2015) - Ma, Lufang; Wang, Xiaoning; Deng, Dongsheng; Luo, Feng; Ji, Baoming; Zhang, Jian
<x xml:space="preserve">Abstract</x> Five desolvated PCPs exhibit efficiency as base catalysts for the Knoevenagel condensation reaction and show size selectivity under solvent-free conditions.